PENGARUH GAYA KEPEMIMPINAN TRANSAKSIONAL, TUNJANGAN KINERJA, DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI KANTOR KESYAHBANDARAN DAN OTORITAS PELABUHAN KELAS I AMBON - Margarita wattimury; Thomas Pentury; Gerrit Pentury (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2018)
The Effect Of Transsactional Leadership style, Performance Allowance,Work Discipline on Employees, Performance at the Office of Martyrdom andPort Authority Class 1 Ambon, This study under the title aimed at examining theeffect of leadership style, performance Allowance, Work Discipline onEmployees, Performance, at the Office of Martyrdom and Port Authority ClassI Ambon aimed at examining the effect of leadership style, performanceallowances and wok discipline on employees’ performance. The population inthis study was the whole employees at the office of Martyrdom and portAuthority Class I Ambon, while the samples take as unit analysis of testing were102 employess. The technique of data collection was by using questionnaire,while the technique of data analysis was multiple regression analysis.Based on data analysis empirically, it was found that transactionalleadership style had positive effects on employees’ performance; performanceallowances had positive effects on employees’ performance; and work disciplineshad positive effects on employees’ performance.